You are given the exponential function g(x) = 3 x . Which option below gives the formula for a new function h created by stretching g by a factor of 3 along the y-axis?

h(x) = 3x+1
h(x) = 3x-1
h(x) = x · 3x+1
h(x) = x · 3x-1

Answers

Answer: First option. h(x)=3^(x+1) g(x)=3^x To strecth g(x) by a factor of 3 along the y-axis we must multiply the function g(x) by 3: h(x)=3 g(x)=3 (3^x)=(3^1)(3^x) Applying multiplication of powers with the same base: (a^b)(a^c)=a^(b+c); with a=3, b=1, and c=x h(x)=3^(1+x) h(x)=3^(x+1)


0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers


More questions